Treatment Results and MRI Study of Percutaneous Repair of Ruptured Achilles Tendon - Kawasoe, Hiroshi; Nagatsuru, Yoshitaka; Murakami, Hiroshi; Matsuoka, Tomomi (Orthopedics & Traumatology, 2004)
Ruptured Achilles tendon has been treated by the percutaneous repair method since 1995 at our hospital. This report discusses the treatment results and MRI study. The subjects were 56 cases (27 males, 29 females), whose average age was 44.6 (range: 27 to 61). Five patients were followed up on MRI by their consent. After three months from operation, average dorsal flexion was 16.4 degrees. On MRI, after one month, the Achilles tendon showed the dumbbell type. After three months, all cases showed the spindle type. Conservative treatment is the established method but this method provides fasten results. A possible reason may be percutaneous repair can draw end to end more than conservative treatment, and comparative early bearing and training of ankle motion provides good range of ankle dorsal flexion.